Rational Choice Theory within the Positivist Paradigm : Contributions and Limits in Explaining Social Phenomena - Yuhannan, Abdullah (Journal of Thai Ombudsman, 2026)
This academic article examines the development of Rational Choice Theory within the framework of positivism by analyzing its basic assumptions, decision-making process, contributions, limitations, and possible applications in explaining social phenomena. The article employs a conceptual approach through a review and synthesis of relevant theoretical works, particularly those of Jon Elster, as well as scholarship in the philosophy of social science, political science, economics, and sociology. The study finds that Rational Choice Theory has made significant contributions to the social sciences by explaining human behavior as a form of decision-making shaped by reason, desires, beliefs, interests, available choices, and constraints. It also contributes to a more systematic and analytically grounded understanding of “reason” in human society. Nevertheless, the theory has been criticized for its reliance on methodological individualism, its emphasis on utility maximization, and its tendency to reduce the complexity of social, cultural, and structural contexts. The article argues that the future development of Rational Choice Theory should move toward a more interdisciplinary orientation, connect individual-level analysis with broader social structures, and apply the theory cautiously to real-world contexts. In doing so, Rational Choice Theory can continue to serve as a valuable framework for explaining, analyzing, and questioning contemporary social phenomena in a more comprehensive manner.